(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
An experiment was conducted at the experimental farm of BINA Sub-station, Gopalganj to determine the effect of spacing on the yield and yield attributing parameters of rice. Four spacings viz. 15 cm × 15 cm, 20 cm × 15 cm, 20 cm × 20 cm and 25 cm × 20 cm were included in the study. The experimental design was a randomized completely block with three replications. Spacing’s 15 cm × 15 cm, 20 cm × 15 cm, 20 cm × 20 cm and 25 cm × 20 cm were adopted 49, 42, 36 and 30 hills per square meter, respectively. Results revealed that different spacing performed significantly differed yield contributing characters (plant height, panicle length, number of effective and non-effective tillers, number of filled and unfilled grain, grain and straw yield of rice. Results indicated that the highest plant height (83.40 cm), panicle length (19.73), number of effective tillers per hill (11.00), number of total grains per panicle (87.73), number of filled grains per panicle (70.53), root length (16.07 cm), root weight (38.00 g per five plants), harvest index (38%), grain yield (4.19 t ha-1) and straw yield (4.50 t ha-1) were found with 25 cm × 20 cm spacing. On the other hand, maximum number of non-effective tillers per hill (1.60) was found in 15 cm × 15 cm spacing. Results of the present study revealed that 25 cm × 20 cm spacing was found to be the best for obtaining maximum grain yield of aus var. Binadhan-19. Res. Agric., Livest. Fish.6(3): 373-378, December 2019